THE INFLUENCE OF ACCOUNTING INFORMATION SYSTEM IMPLEMENTATION, FINANCIAL LITERACY, AND INTERNAL CONTROL ON THE QUALITY OF FINANCIAL STATEMENTS OF TANGERANG REGENCY MSMES - Ervina Yennie Permananingrum; Abu Naim; Annisa Risqi Sulistya Kusuma Wardhani; Fachmi Al Faroqi; Andika Mugi Gumilang; Nor Fatah Ulinnuha; Sapriyadi; Ahmad Pauji (RADJA PUBLIKA, 2025)
MSMEs, or micro, small, and medium-sized enterprises, are essential to Tangerang Regency's economic growth. However, a lot of MSME owners still struggle to produce high-quality financial statements because of poor internal control, low accounting awareness, incomplete technology utilisation, and inaccurate records. Their capacity to evaluate business situations, control cash flow, and develop long-term strategies is impacted by this circumstance. Thus, the purpose of this study is to examine how internal control, financial literacy, and the use of Accounting Information Systems (AIS) affect the quality of MSMEs' financial statements in Tangerang Regency. Purposive sampling was used to identify 200 MSME respondents for this quantitative study. A standardised Likert-scale questionnaire was used to gather the data, and SPSS was used for analysis, which included multiple linear regression and traditional assumption tests. The model is suitable for additional study when classical assumption testing reveals that the data satisfy the conditions for autocorrelation, heteroscedasticity, multicollinearity, and normality. According to the regression results, the quality of financial statements is positively and significantly impacted by AIS adoption (β = 0.315; Sig. = 0.000), financial literacy (β = 0.291; Sig. = 0.000), and internal control (β = 0.348; Sig. = 0.000). The biggest predictor is internal control, suggesting that regular assessments, job segregation, and monitoring systems are essential to guaranteeing the dependability and correctness of MSME financial reporting. Additionally, the F-test shows that all three variables have an impact on financial statement quality at the same time (Sig. = 0.000). The three variables account for 53.9% of the variation in financial statement quality, whereas other factors not included in the model account for 46.1%, according to the coefficient of determination (R² = 0.539).